Transcranial direct current stimulation in individuals with severe traumatic brain injury in the subacute phase: a case series - Cordeiro, Barbara Naeme de Lima; Rocha, Jader Vinicius Da Silva; Kuster, Elizangela; Thibauth, Aurore; Nascimento, Lucas Rodrigues; Swank, Chad; Arêas, Guilherme Peixoto Tinoco; da Silva Filho, Walter Gomes; Anhoque, Carolina Fiorin; Silva Paiva, Wellingson; Buarque, Jéssica Costa; Arêas, Fernando Zanela (Frontiers in Human Neuroscience, 2025)
The aim of this study is to report clinical cases of patients with severe traumatic brain injury (TBI) who underwent transcranial direct current stimulation (tDCS) in the subacute phase. We hypothesize that tDCS will improve the functional and cognitive recovery of patients. 5 men, admitted with severe TBI, and Glasgow Coma Scale (GCS) score ≤ 8 on admission or at some point during hospitalization, were in the subacute phase of the trauma (between 2 and 16 weeks). Participants received 5 sessions of tDCS every day. The results were measured at the beginning and at the end of the 5 sessions. The application of tDCS with an active electrode (anode) was applied to the region of the left dorsolateral prefrontal cortex (LPFC - F3) and the cathode was positioned over the contralateral supraorbital area. Clinical outcomes were measured through cognitive assessment, Mini Mental State Examination (MMSE), mental health and depression, Hospital Anxiety and Depression Scale (HADS-A), pain, visual analogue scale (VAS), Functional Independence Measure (FIM), Rancho Los Amigos Scale (RLAS) and Glasgow Outcome Scale - Extended (GOS-E), were applied to classify the patient’s condition. For characteristics of participants and findings results, descriptive statistics were presented as mean ± Standard Deviation (SD). The results after the tDCS intervention show substantial improvement in the assessed. The research demonstrates the potential benefits of using tDCS in patients with TBI, but also provides a practical basis for applying these techniques in clinical settings.